Sustainable Aromatherapy Pouch with Natural Lemon and Rosemary Scents - Tomaroy, Julianne Caitlin; Cadayona, Divine Mhargarette; Partosa, Harley; Bangalando, Maria Antonio Kyrell; Grefaldia, Rhea Roxana (Journal of Interdisciplinary Perspectives, 2025)
This study examines a novel approach to aromatherapy, utilizing Orbeez—small, water-absorbing beads—as carriers for essential oils. While lemon and rosemary are known for their calming effects, no research has been done on using Orbeez to diffuse these scents. To combine relaxation with sustainability, the beads were placed in pouches made from recycled paper, creating an eco-friendly product that provides quick stress relief. To assess the usability, durability, and effectiveness of the pouch, 60 participants used the aromatherapy pouch and completed a descriptive survey questionnaire. The survey included indicators that measured how easy the pouch was to use, how well it held up over time, and its effectiveness in providing emotional comfort. Results showed strong positive feedback. Portability received a high mean score of 4.45, while overall user-friendliness was rated at 4.32. For durability, the pouch remained functional after repeated use (x̄ = 4.07), although some users reported minor issues, such as tearing. The recycled materials were still seen as generally durable (average: 3.92). Regarding effectiveness, participants reported a calming effect during anxious moments (x̄ = 4.15), and many found the blend of lemon and rosemary to be especially soothing (x̄ = 4.58). The study presents a practical, low-cost, and sustainable tool for emotional support using natural ingredients and recyclable materials. Its simplicity, portability, and immediate effect make it suitable for everyday use, especially in moments of stress or discomfort. Future research is recommended to investigate the duration of the scent's effectiveness, how different users respond to the aromatherapy pouch, and how it can be improved for enhanced durability and broader applicability.